Questionnaire Analysis of the Methodology Issues Concerning Bilingual Education at Secondary Technical Schools (Training and Practice : Journal of Educational Sciences, 2015)
Bilingual education has to face special difficulties in the field of professional training as it could become impossible without appropriate teaching materials and elaborated methods. These problems can, first of all, be solved by considering the participants’ needs more and more intensively. In the first and last year of the English-Hungarian bilingual classes at Szombathely Secondary Technical School for Trade and Catering, surveying the demand took place in the form of an online questionnaire so that the database could be made user-friendly. Besides the questions concerning learning techniques (e.g. time spent on learning, frequency of using Internet), students also had the opportunity to give their opinion on the database. The present paper reports on the results of this survey while highlighting the differences between the classes involved.